Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1590/s0101-81752001000300011
|View full text |Cite
|
Sign up to set email alerts
|

Morcegos do Parque Nacional do Iguaçu, Paraná (Chiroptera, Mammalia)

Abstract: lt's presented a survey of bat species from Parque Nacional do Iguaçu, Paraná State, it has a area of 170.086,76 ha, located in west ofthe Paraná State. A total of 1403 individuais belonging to 26 species were registred

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 3 publications
3
9
0
5
Order By: Relevance
“…The present study registered lower values of species richness when compared to others carried out in this state, possibly due to the fact that these surveys used other capture methods in the other studies. For example, in the region of Londrina municipality, in 680 ha of forest remnants, 42 species were registered (Reis et al, 2008); in the 52,000 ha in the Telêmaco Borba municipality, 22 species were observed (Reis et al, 1999); and, in the 170,000 ha of Parque Nacional do Iguaçu, in the Foz do Iguaçu municipality, 26 species were sampled (Sekiama et al, 2001). *Gardner (1977) The existence of few remnants, caused by habitat fragmentation (Mikich and Silva, 2001), may generate loss of species in the region due to anthropogenic changes in the habitats (Reis and Muller, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The present study registered lower values of species richness when compared to others carried out in this state, possibly due to the fact that these surveys used other capture methods in the other studies. For example, in the region of Londrina municipality, in 680 ha of forest remnants, 42 species were registered (Reis et al, 2008); in the 52,000 ha in the Telêmaco Borba municipality, 22 species were observed (Reis et al, 1999); and, in the 170,000 ha of Parque Nacional do Iguaçu, in the Foz do Iguaçu municipality, 26 species were sampled (Sekiama et al, 2001). *Gardner (1977) The existence of few remnants, caused by habitat fragmentation (Mikich and Silva, 2001), may generate loss of species in the region due to anthropogenic changes in the habitats (Reis and Muller, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…A Ilha Mutum se encontra na Área de Proteção Ambiental Federal das Ilhas e Várzeas do Rio Paraná (Mikich & Bérnils 2004). (Sekiama et al 2001, Reis et al 2000e 2003, Bianconi et al 2004, Peracchi et al 2006. O exemplar foi seguramente identificado apresentando os caracteres diagnósticos da espécie (LaVal 1973, Vizotto & Taddei 1973, Barquez et al 1999, López-González et al 2001.…”
Section: Methodsunclassified
“…Considering the sampling effort applied, which was small, the richness obtained was satisfactory. Studies in fragments of semi-deciduous seasonal forests or urban areas in other municipalities of Paraná have obtained similar or higher number of species, but using a much higher sampling effort ( The small sample obtained in the forest fragment of the rural property does not represent well the local bats community, a higher sampling effort (Reis & Muller 1995, Sekiama et al 2001, Bianconi et al 2004, Arnone & Passos 2007, Graciolli & Bianconi 2007, Ortêncio-Filho & Reis 2009, Gazarini & Pedro 2013.…”
Section: Discussionmentioning
confidence: 99%